8A.06: DIFFERENTIAL IMPACT OF ANEMIA ON LEFT VENTRICULAR FILLING PRESSURE BETWEEN SUBJECTS WITH AND WITHOUT HYPERTENSION. RESULTS FROM A MULTICENTER, COHORT STUDY. (June 2015) - Cho, I.; Kim, M.A.; Shim, W.J.; Park, S.M.; Kim, Y.H.; Na, J.O.; Shin, M.S.; Kim, Y.J.; Yoon, H.J.; Cho, Y.K.; Kim, S.E.; Hong, K.S.; et al.
Abstract : Objective: It has been reported that anemia is associated with elevated left ventricular (LV) filling pressure and structural changes in hypertensive patients. However, effect of mild to moderate anemia on LV structure or function in non-hypertensive population is not well known. The aim of the study was to evaluate impact of anemia on LV functional changes in patients with and without hypertension among participants in Chest Pain in Korean Women's Registry. Figure. No caption available. Design and method: Chest Pain in Korean Women's Registry is a large, multicenter registry including demographic data, symptom, psychosocial variables, coronary angiographic and echocardiographic data and a variety of blood determinations. As a part of the core data, 916 patients with preserved LV ejection fraction constituted the study population. Echocardiographic data were obtained including LV mass index, early mitral inflow (E) velocity and early mitral annular (e') velocity. E/e', a parameter for the LV filling pressure, was calculated. Results: Hypertension was observed in 407 patients (44%). Coronary artery disease (CAD) was diagnosed in 353 patients (39%). There were significant differences in prevalence of CAD, age, serum creatinine, blood pressure, left atrial size, LV mass index, E velocity, e' velocity and E/e' between the patients with and without hypertension. There was negative correlation between hemoglobin level and E/e' in hypertensive patients (r = −0.182, p = 0.001), but there was no significant relation between the variables in non-hypertensive patients. In addition, E/e' proportionally increased according to normal, mild to moderate anemia and severe anemia only in hypertensive patients (p for trend = 0.002). On multivariate analysis, E/e' demonstrated independent correlation with presence of anemia in hypertensive patients, even after adjusting age, diabetes mellitus, CAD, creatinine and total cholesterol in hypertensive patients (p = 0.019). Conclusions: Anemia is associated with raised LV filling pressure only in patients with hypertension, but not in those without hypertension from the large registry of women with high prevalence of CAD.